THE GINI CONCENTRATION INDEX: A REVIEW OF THE INFERENCE LITERATURE. (12th December 2016) - Giorgi, Giovanni Maria; Gigliarano, Chiara
Abstract: More than a century ago, Corrado Gini proposed his well‐known concentration index for measuring the degree of inequality in the distribution of income and wealth. His index is still extremely relevant and widely used in several fields of research and application. In this paper, we focus on the inferential properties of the Gini index, and discuss the main directions of analysis proposed in the literature. The aim of the paper is to provide a comprehensive review of the main developments on the inferential aspects of the Gini concentration ratio. We feel that this work can provide a valuable contribution to those scholars who are approaching the large amount of literature on the inferential properties of the Gini index.